DAYA TARIK BAGI WISATAWAN BERSEPEDA DI PEDESAAN BALI - Anak Agung Gde Oka Geria; I Gusti Ngurah Agung Suprastayasa (UHN IGB Sugriwa Denpasar, 2021)
This writing is descriptive qualitative study which is aimed to identify the tourism interests and supporting facilities needed by international tourists taking a cycling package tour in Petak Kaja Village. The study is a type of village or rural area tourism development based on the theory of sustainable community based tourism. Data were collected through interview with 15 tourists taking cycling tour program in Peta Village. The result shows that the tourists taking part in this cycling package tour found some village attributes such as the local people, their daily life, the landscape beauty, village rice fields, local ceremonies, village houses, temples and schools are interesting. Meanwhile environment cleanliness, village traffic and quality of village roads are less interesting. The landscape beauty is most interesting and the village traffic is the least interesting. They urgently need clean and hygienic toilets and clear and good quality of water which they can use in the houses of local people. The results showed brought about some practical implication namely the need to provide and improve the facilities needed by the tourist and the cleanliness.